2023
DOI: 10.52403/ijrr.20230102
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Sleep Quality and Learning Achievement in Junior High School Students in Denpasar

Abstract: Background: Learning is defined as a process of continuous development in various aspects of a person. Although various literatures have examined the relationship between sleep quality and learning activities, there are still few studies that discuss the relationship between sleep quality and learning achievement in students. Therefore, the authors want to determine the relationship between sleep quality and learning achievement achieved by junior high school students in Denpasar. Method: This study was an ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…However, it is essential to note that one study found no significant relationship between sleep quality and learning achievement in junior high school students, as cognitive factors like motivation, IQ level, and study habits also play crucial roles in academic performance (Putra et al, 2023).…”
Section: Sleep Hours Of Studentsmentioning
confidence: 98%
See 1 more Smart Citation
“…However, it is essential to note that one study found no significant relationship between sleep quality and learning achievement in junior high school students, as cognitive factors like motivation, IQ level, and study habits also play crucial roles in academic performance (Putra et al, 2023).…”
Section: Sleep Hours Of Studentsmentioning
confidence: 98%
“…Open Access: https://ejournal.papanda.org/index.php/edukasiana/ The results of this study contradict the existing literature that there is a relationship between sleep hours and academic performance. Among the respondents, an astonishing 67% of SHS students disclosed that their sleep duration falls within the range of more than 4 to 6 hours per day-a period that is often deemed inadequate for optimal cognitive function and scholastic success (Putra et al, 2023).…”
Section: Sleep Hours Of Studentsmentioning
confidence: 99%